An architecture to facilitate interoperability of Discrete Event System Specification and Coalition Battle Management Language simulation models. (January 2016) - Hosang, Elizabeth; Wainer, Gabriel A
The Joint Command, Control and Communications Information Exchange Data Model, Coalition Battle Management Language and Military Scenario Definition Language define formatted schemas that have been developed for use in military simulations. The Discrete Event System Specification (DEVS) is used to create models whose behavior is defined in response to events in the simulated environment. The RESTful Interoperability Simulation Environment (RISE) provides a web-based interface for executing DEVS models. DEVS models can be used to simulate systems as diverse as natural disasters and traffic patterns. We present an application that uses formatted messaging to interact with a DEVS model running on the RISE server. The purpose of this is to demonstrate that a DEVS model can be executed as part of a larger, web-enabled synthetic environment, such as a military planning exercise.